2021
DOI: 10.3390/ijms22073450
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of White Spot Syndrome Virus: Promise in Shrimp Seedling Culture

Abstract: Rapid production of prawn (Litopenaeus vannamei) under artificial pressure can result in a series of obvious challenges and is vulnerable to serious losses related to aquatic environmental issues and the unrestrained outbreak of white spot syndrome (WSS). However, to date, there are no therapeutic strategies to contain the spread of the virus. Here, we synthesized 27 coumarin deriv-atives and evaluated their anti-white spot syndrome virus (WSSV) activity in L. vannamei larvae. We demonstrated that electron-wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Surprisingly, previous study found that paeoniflorin and esculin had anti‐WSSV effects in shrimp, which could be developed as lead compounds 96,128 . Interestingly, esculin belongs to the coumarin class of compounds and researchers have screened several coumarin derivatives with anti‐WSSV activity in previous studies 129–131 . Derivatives of coumarin were also selected for anti‐WSSV horizontal transmission experiments and were found to be effective in inhibiting WSSV horizontal transmission, providing a primer for their application 100 .…”
Section: Antiviral Effect Of Medicinal Plants and Their Active Ingred...mentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, previous study found that paeoniflorin and esculin had anti‐WSSV effects in shrimp, which could be developed as lead compounds 96,128 . Interestingly, esculin belongs to the coumarin class of compounds and researchers have screened several coumarin derivatives with anti‐WSSV activity in previous studies 129–131 . Derivatives of coumarin were also selected for anti‐WSSV horizontal transmission experiments and were found to be effective in inhibiting WSSV horizontal transmission, providing a primer for their application 100 .…”
Section: Antiviral Effect Of Medicinal Plants and Their Active Ingred...mentioning
confidence: 99%
“…96,128 Interestingly, esculin belongs to the coumarin class of compounds and researchers have screened several coumarin derivatives with anti-WSSV activity in previous studies. [129][130][131] Derivatives of coumarin were also selected for anti-WSSV horizontal transmission experiments and were found to be effective in inhibiting WSSV horizontal transmission, providing a primer for their application. 100 Notably, previous study investigated the potential application of cuminaldehyde, a Chinese herbal medicine extract commonly found in cumin essential oil, in the prevention and treatment of WSSV.…”
Section: Antiviral Effect Of Medicinal Plants and Their Active Ingred...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a lack of effective treatment strategies against the disease. In addition to the lack of efficacious treatments or preventative measures, complex infection transmission routes and its broad host range make its eradication from affected ponds difficult, 10 which further intensifies the potential damage 11 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the lack of efficacious treatments or preventative measures, complex infection transmission routes and its broad host range make its eradication from affected ponds difficult, 10 which further intensifies the potential damage. 11 The WSSV viral genome is a circular, double-stranded DNA ranging between 290 and 307 kb in different isolates. 12,13 Moreover, it has been classified as the only member of the genus Whispovirus belonging to the Nimaviridae family owing to its unique genetic and morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%